Single-cell analysis of diverse immune phenotypes in malignant pleural effusion - Zhong-Yin Huang; Ming-Ming Shao; Jian-Chu Zhang; Feng-Shuang Yi; Juan Du; Qiong Zhou; Feng-Yao Wu; Sha Li; Wei Li; Xian-Zhen Huang; Kan Zhai; Huan-Zhong Shi (Nature Communications, 2021)
Detailed immune cell subset identification in human lung (malignant pleural effusion) MPE is important for diagnosis and prognosis. Here the authors use single cell RNA sequencing to identify immune cell types within MPE and show differential gene expression compared to circulating immune cells in blood.